Papers Submited of Admission - khosro khademi-Kalantari (Shahid Beheshti University of Medical Sciences, 2022)
The purpose of this letter to the editor is to provide an insight into the editorial process from submission to publication. There are many guidelines for authors before submission for the manuscript preparation to help their manuscript be processed faster; however, if the editors do not follow them, it will be less likely to process the submissions in a short time. After submission, the chief editor consults with the associate editors to decide whether to reject the manuscript or send it to the reviewers. If not rejected, it will be carefully assessed by a checklist in terms of different technical issues based on the instructions for authors exist in the journal website. The authors should ensure that they comply with instructions. This can speed up the process. A template is usually available for them in this regard. The second step is to select qualified reviewers for the manuscript. This is a very important step in the editorial process. The reviewers should be invited based on the relevance of their profession to the topic of the submitted manuscripts, and also based on their previous reviews. Since the "Scientific Journal of Rehabilitation Medicine" is a multidisciplinary journal, a large group of professionals are cooperating in the reviewing process.  The reviewer comments are sent back to the authors, and the amendments and responses of authors should be sent back to the reviewers. This process may be repeated for several times until the reviewers are satisfied with the responses and revisions of authors.